MEANS OF SOCIAL ECONOMIC REFORM IN ISLAM - Abul Firdaus Bayinat Basha Al Bajali (International Journal For Research In Business, Management And Accounting, 2018)
Worship includes every human movement in life, and accordingly a person’s quest for gain is worship, and he is rewarded for it as long as he adheres to what he is obligated to do in it. The research has been called just earning; Because the meaning of justice is a comprehensive meaning to address many things, it is more general from the word of the halal or crusher, and human must be amounting to himself and with others, Allah says: you remember), In this research, I dealt with the importance of the means leading to reforming and achieving the interests of society economically, and the dangers of globalizing the culture of earning. For this reason, I extrapolated the verses in which the conditions of earning are mentioned in the Noble Qur’an, using the inductive method, then I interpreted the verses and explained hadiths, criticism and deduction. Using the analytical method, then I showed the teachings to which the verses guide us, which must be applied in dealing with people through the applied approach.